A SELF-REFLEXIVE PRAXIS: CHANGING ATTITUDES TOWARDS MANUSCRIPT AND TEXT IN EARLY CHINA. (September 2019) - Krijgsman, Rens
Abstract: This article examines the attitudes of Warring States textual witnesses to the increase in presence of and reliance on bamboo manuscripts in communicating knowledge. Based on a rereading of transmitted materials and four manuscript texts ( *Wuwang Jianzuo A and B, *Baoxun, and the Zhou Wuwang you ji ) from the Warring States period, I analyze how contemporaries dealt with questions about the status of (manuscript) texts, their use and transmission, their trustworthiness, and their ability to preserve knowledge. These are texts that talk about themselves. They remark upon the physicality of text and the act of writing, the problem of oral and written transmission, and the differences in the ability of memory and manuscripts to store, hide, and reveal knowledge. I argue that these different reflections reveal a change in the predominant medium of communicating knowledge towards an increased reliance on bamboo manuscripts gradually and partially replacing traditional knowledge practices. 提要: 本文探討戰國時期文本對寫本廣泛使用的反思。基於重讀傳世文獻和四篇出土文獻（分別為：上博簡《武王踐祚》甲、乙本，清華簡《寶訓》和《周武王有疾周公所自以代王之志》），本文討論戰國時期人如何看待寫本和文本的地位、它們保存信息的功能和可信度，以及寫本的使用與流傳、傳授。這些文本的特點呈現在"自我反思"。它們的內容正是講述自己作為寫本的物質性、書寫、口頭和書寫傳授的問題，以及記憶和寫本在保存、隱藏和傳達信息能力上的區別。我認為這些"反思"呈現了傳達信息的主要媒體的轉變：從傳統意義下的知識實踐到逐漸依賴寫本載體。